RISK MANAGEMENT IN ANAESTHESIA - Gilani, Syed Mushtaq (Journal of Ayub Medical College Abbottabad, 2002)
Since anaesthesia is rarely a therapeutic intervention by itself, but merely a supportive measure of a primary surgical intervention so the losses from the mishaps appear to be more catastrophic in nature to the health consumer. It has been suggested that anaesthesia consequently puts patients at risk while offering no direct curative benefit1. Just a few decades ago, an unexpected death or serious mishap during anaesthesia and surgery was viewed as a tragic but unavoidable event by patients and their families and by the public at large. For a lot of reasons, the public expectation has changed radically within one generation. Today, an anaesthetic accident or death is rarely accepted as fate. Now the average patient in reasonable health who enters the hospital for surgery will not expect to die or have serious accident from causes related to anaesthesia. A risk is no longer acceptable if it leads to loss of life or major impairment as a result of technical or human failure especially when such failure is thought to be avoidable. The public expectation, then, is for the conduct of anaesthetic practice in such a manner that anaesthesia is associated with a near-zero mortality and morbidity. This public expectation is a fact in our professional lives and we must examine how we can work towards the high degree of favourable outcome expected by patients and their families. In addition to this public expectation, our professional aim should be to strive towards same goal with the devotion and skill of those practicing the science and art of anaesthesia. We must define past and current states of anaesthesia- related risk and then try to identify how to achieve the goal of substantially reducing these risks in future. Recognition of avoidable technical and human errors makes regrettable but important contribution to overall anaesthetic mortality and morbidity2. The goal of reducing the anaesthesia risk is achievable. Individual vigilance and constant teaching and training will reduce the mortality and morbidity. We must reduce avoidable accidents wherever we can do so- especially when it can be done at a low cost. Effectiveness of equipping the operation rooms is difficult to evaluate. Before taking action to reduce risk we always do not need to know precise data. If it is known that accidental disconnection of anaesthetic apparatus cause deaths, we do not need to know whether frequency is 1:10,000 or 1:100,000 before we do something about it especially when likely improvements in outcome can be achieved inexpensively and simply3. Anaesthetic mishaps may appear attributable to mechanical apparatus or to the anaesthesiologist administering anaesthetic. Mechanical failure may also be the result of human error. The pre-flight check list routinely employed by the pilots is worthy of practice and its analogue for anaesthetic system is receiving broader use. The use of various monitoring devices that aid in the detection of potentially critical events do not have to replace the use of the anaesthesiologist’s senses, but they augment them. Risk, in the medical setting, is generally defined as any exposure in the hospital to potential injury or financial loss4. The development of risk management process in anaesthesia will assure quality control in anaesthesia practice. This means the creation of formalised programme within the department to Identify, asses and resolve the wide range of factors contributing to preventable mishaps under the control of anaesthetic staff. Quality assurance and risk management protocols should be vigorously and consistently implemented to reduce morbidity and mortality associated with anaesthetic administration. The risk management process, although simple in approach, requires a firm commitment of time, staff resources, and total medical staff support to be a truly effective and result-oriented program. Anaesthesia services at teaching hospitals should strive to use regularly scheduled sessions for example conference and grand rounds to provide ongoing risk management education throughout the academic year. The educational process can also give staff the opportunity to participate in the review and resolution of problems in their department concurrent with the orientation of new anaesthesiology residents and fellows. The author hopes that opportunities and funding will be provided by the concerned authorities to allow necessary program to be developed so that action may be taken than just more writing about the problems.